Hydrogeochemical process and coal mining-motivated effect on the hydrochemistry for the groundwater system in mining area of Western China - Zeng, Yifan; Wu, Qiang; Mei, Aoshuang; Wang, Lu; Yin, Wenbin; Yang, Lei; Zhao, Di; Meng, Shihao; Gao, Hongfei (Journal of geochemical exploration, 2024)
The Jurassic coalfield in the mining area of western China exhibits a multi-layered groundwater system. However, it is subject to an arid and semi-arid climate with limited water resources. Consequently, the ecological environment is highly vulnerable, and the chemistry and quality of groundwater may be influenced by multiple factors. This study systematically the coal mining-motivated effect on the hydrochemistry and water quality of the groundwater system, using the Caojiatan Coal Mine as a case study. The analysis incorporates a combination of the self-organizing maps (SOM), entropy-weighted water quality index (EWQI), and traditional hydrochemical analysis methods. After coal mining, there was an increase in the proportion of HCO3-Ca and HCO3-Mg in the groundwater samples of J2z, J2y4, and J2y5. The groundwater is controlled by cation exchange as a whole. The J2y4 and above groundwater is influenced by both the dissolution of carbonate and silicate rocks before coal mining. After coal mining, the Quaternary and J2a groundwater in the western wing is primarily influenced by the dissolution of carbonate rocks; the J2z, J2y4 and J2y5 groundwater is primarily governed by the dissolution of silicate rocks and the oxidation of FeS2; the J2y3 and below groundwater is primarily controlled by the dissolution of evaporate rocks. The resulting dilution effect after coal mining and the implementation of measures for the discharge of treated mine water make the groundwater quality of the J2y4 and higher aquifers tend to be better. The research findings serve as a valuable reference for promoting the sustainable development and protection of groundwater resources not only in the study area but also in other coal mines. •SOM offered valuable insights to clarify the diverse hydrochemical characteristics.•The hydrochemical process exhibited changes before and after coal mining.•Coal mining led to an improvement in groundwater quality due to dilution effect.•The coal mining-motivated effect on the hydrochemistry of groundwater system was systematically investigated.